PENGARUH SKARIFIKASI DAN HORMON GIBERELIN (GA3) TERHADAP DAYA KECAMBAH DAN PERTUMBUHAN BIBIT PALEM PUTRI (Veitchia merillii) - Rita Elfianis; Siti Hartina; Indah Permanasari; Jully Handoko (Jurnal Agroteknologi, 2019)
Christmas palm is a plant that has high economic value as an ornamental plant and is in great demand. Christmas palm seeds begin to germinate 3-4 weeks after planting, slow germination because of to seeds experiencing physical dormancy. To break dormancy can be done by scarification and immersion GA3. The purpose of this study was to determine the effect of scarification and GA3 on the germination and growth of christmas palm seedlings and the interaction between the two treatments. This research was carried out from December 2017 to March 2018 on experimental Field and Agronomy Laboratory Faculty of Agriculture and Animal Science State Islamic University Sultan Syarif Kasim Riau. The method used Randomized Complete Block Design (RCBD) with two factors and four replications. The first factor was the scarification (control and with scarification) and the second factor is immersion GA3 (0 ppm, 150 ppm, 300 ppm and 450 ppm). The results showed that scarification by means of sandpaper can increase the growth rate and height of the christmas palm plant.The dipping of GA3 with concentration of 450 ppm for 2 hours is the best concentration for growth speed. There was no interaction between scarification and GA3 immersion on all observational parameters both in germination and in the nursery of chritmas palm plants on the land.